Modelo agrometeorológico na estimativa da produtividade de duas variedades de café arábica considerando a variabilidade espacial - de Assis Silva, Samuel; de Souza Lima, Julião Sares; de Oliveira, Rone Batista [UNESP] (My University, 2011)
The purpose of this study was to estimate the varieties of coffee Arabic Catucáand Catuaí productivity, in Zona da Mata, Minas Gerais, through agrometeorological mathematical models, considering the spatial variability of productivity in the area. The samplings were georrefered building an irregular grid, totalizing 50 samplings per area. After that, geostatic analysis was made to quantify spatial dependence degree of the real values and the estimated productivity. According to the classification, the models superestimated the productivity for the two varieties.

O objetivo deste estudo foi estimar a produtividade das variedades de café arábica, Catucaí e Catuaí, na região da Zona da Mata de Minas Gerais, através de modelos matemáticos agrometeorológicos, considerando a variabilidade espacial da produtividade nas áreas. Os pontos amostrais foram georrefenciados para a construção de uma malha irregular, totalizando 50 pontos por área. Em seguida, procedeu-se a análise geoestatística para quantificar o grau de dependência espacial dos valores reais e os estimados de produtividade. De acordo com a classificação, o modelo superestimou a produtividade para as duas variedades analisadas.
Agrometeorological model estimating the productivity of two varieties of arabic coffee considering the spatial variability
Keywords: Forecast of harvest; Geoestatistic; Precipitation; agricultural production; agrometeorology; coffee; estimation method; forecasting method; geostatistics; harvesting; numerical model; precipitation (climatology); spatial variation; Brazil; Minas Gerais